Lauku dzīve Rūdolfa Blaumaņa un Tomasa Hārdija literārajos darbos - Drebeinieka, Ilona (Latvijas Universitāte, 2008)
Šis bakalaura darbs pēta 19. gadsimta Latvijas un Anglijas lauku dzīves aprakstu Rūdolfa Blaumaņa literārajos darbos “Indrāni”, “Pazudušais Dēls” un “Baltais”, kā arī Tomasa Hārdija romānos “Tālu prom no trokšņainā pūļa”, “Mūžīgā atgriešanās”, „Kāsterbridžas mērs” un “Tesa no d’Erbervilu cilts”. Pirmajā nodaļā autore aplūko lauku tēmas sastopamās angļu un latviešu 19. gadsimta literatūrā, kā arī piemin šī perioda ievērojamākos angļu un latviešu rakstniekus. Otrā nodaļa ir veltīta svarīgākajām pārmaiņām ekonomikā, sabiedrībā un lauku dzīvē Lielbritānijā un Latvijā 19. gadsimtā, uz kuru fona tiek aprakstīti notikumi galveno varoņu dzīvēs. Darba nodaļas analīzē Hārdija un Blaumaņa lauku dzīves individuālo uztveri Anglijā un Latvijā, kā arī piedāvā galveno varoņu raksturojumu, tikumu un attiecību attēlojumu.

The present Bachelor Paper explores the depiction of the Latvian and English country life of the 19th century in Rūdolfs Blaumanis’s literary works “Indrāni”, “Pazudušais Dēls” (“The Prodigal Son”), and “Baltais” (“The White”), and Thomas Hardy’s novels “Far from the Madding Crowd”, “The Return of the Native”, “The Mayor of Casterbridge”, and “Tess of the D’Urbervilles”. In the first chapter, the author of the paper discusses rural themes which can be encountered in the English and Latvian literary works of the 19th century, as well as mentions the most prominent English and Latvian writers of the given period. The second chapter gives a brief account on the main changes in economy, society, and landscape in Great Britain and in Latvia in the 19th century, which served as the background for the selected literary works. The practical parts of the paper analyzes Hardy and Blaumanis’s individual perception of the English and Latvian country life and representation of human relations and morals, as well as presents the portrayals of the main country people’s characters in the selected literary works. The conducted research allows the author to conclude that the selected novels by Thomas Hardy and Rūdolfs Blaumanis masterfully depict the country life in its full diversity against the changing economic, social and agricultural backgrounds of the 19th century Latvia and Great Britain.
Country Life in Rūdolfs Blaumanis and Thomas Hardy's Fiction
Keywords: Filoloģija